2011
DOI: 10.1002/lary.22365
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of large-diameter dilatation in cricopharyngeal dysfunction

Abstract: In the largest series of esophageal dilatation for cricopharyngeal dysfunction in the literature, we found large-bore bougienage to have significant utility due to its efficacy, ease of use, and safety when compared to other modalities such as botulinum injection, balloon dilatation, and cricopharyngeal myotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…Clary et al suggested CP bougie dilatation as a first surgical step. They advocate this two‐step approach for two reasons: 1) if dysphagia resolves, the patient can avoid a more morbid myotomy, and 2) if patient experiences no relief, it can suggest a need for further workup to evaluate other causes of dysphagia …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clary et al suggested CP bougie dilatation as a first surgical step. They advocate this two‐step approach for two reasons: 1) if dysphagia resolves, the patient can avoid a more morbid myotomy, and 2) if patient experiences no relief, it can suggest a need for further workup to evaluate other causes of dysphagia …”
Section: Discussionmentioning
confidence: 99%
“…The range of BoT doses reported per injection varies from 10 U to 100 U . Bougienage has been used in the treatment of anatomic esophageal strictures for decades . The commonly used approaches are bougies, wire‐guided polyvinyl dilators, air‐filled pneumatic dilatation, and water‐filled balloon dilatation with or without endoscopy guidance …”
Section: Introductionmentioning
confidence: 99%
“…This method has a limitation that it should be performed only by an endoscopy specialist. Clary et al [8] used a larger 60-Fr esophageal dilator. This also needs a laryngoscopist; and patients should undergo sedation or general anesthesia [8].…”
Section: Discussionmentioning
confidence: 99%
“…Clary et al [8] used a larger 60-Fr esophageal dilator. This also needs a laryngoscopist; and patients should undergo sedation or general anesthesia [8]. Furthermore, minor complications, such as mucosal tear, laryngospasm, and low postprocedural oxygen saturation, were observed in 10% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…3 Once a CP bar becomes symptomatic, it is an important cause of oropharyngeal dysphagia, causing a restrictive defect at the pharyngoesophageal junction. [6][7][8] At our institution, we initially perform Savary dilation for symptomatic CP bars. Dilation of a CP bar can be a safe and effective means of nonsurgical treatment as this patient population has high morbidity and is at a higher risk of surgical complications.…”
mentioning
confidence: 99%